Cardio-Pulmonary Parasitic Nematodes Affecting Cats in Europe: Unraveling the Past, Depicting the Present, and Predicting the Future - Traversa, Donato; Di Cesare, Angela (Frontiers in Veterinary Science, 2014)
Various cardio-pulmonary parasitic nematodes infecting cats have recently been fascinating and stimulating the attention of the Academia, pharma companies and veterinary practitioners. This is the case of the metastrongyloids: Aelurostrongylus abstrusus and Troglostrongylus brevior, the trichuroid: Capillaria aerophila (syn. Eucoleus aerophilus), and the filarioid: Dirofilaria immitis. Apparently, these parasites have been emerging in several European countries, thus gaining an important role in feline parasitology and clinical practice. Under a practical standpoint, a sound knowledge of the biological, epidemiological and clinical impact of cardio-respiratory parasitoses affecting cats, in addition to a potential risk of introduction, establishment and spreading of “new” parasites in Europe is mandatory in order to understand the present and future impact for feline medicine and to address new strategies of control and treatment. The purpose of the present article is to review the current knowledge of heartworm and lungworm infections in cats, discussing and comparing past and present issues, and predicting possible future scenarios.